Transcriptome analysis of the uniparous and multiparous goats ovaries. (20th September 2016) - Wang, LJ; Sun, XW; Guo, FY; Zhao, YJ; Zhang, JH; Zhao, ZQ
Contents: Transcriptome analysis of Inner Mongolia Cashmere goat and Dazu black goat generated 38, 772, 947 and 38, 771, 668 clean pair end reads, respectively, which were assembled into 72, 422 and 80, 069 unigenes by Trinity, respectively. For Inner Mongolia Cashmere goat, 26, 051 and 10, 100 unigenes were assigned to gene ontology (GO) categories and clusters of orthologous groups, respectively. A total of 32, 772 unigenes can comment to SWISS‐Prot database, and the Kyoto Encyclopedia of Genes and Genomes Pathway database (KEGG) mapped 24, 420 unigenes. While annotating the unigenes about Dazu black goats, we found 29, 444(45.42%), 11, 271 (38.28%), 36, 910(56.94%) and 27, 766 (42.83%) unigenes were assigned to GO database, COG database, SWISS‐Prot database and KEGG database, respectively. In addition, we performed the bioinformatics analysis of gene expression profiling aimed at the ovarian transcriptome difference between Inner Mongolia Cashmere goat and Dazu black goat. We obtained a sequencing depth of over 5.5 million and 5.8 million tags. There were 1, 133 DEGs between two species, of which 632 genes upregulated in the Dazu black goat and 501 genes downregulated compared with which in Inner Mongolia Cashmere goat. By annotating the 1, 133 DEGs into KEGG database, we found 525 DEGs. And there were 68 DEGs annotated in metabolic pathways, 31 DEGs annotated in ribosome, 28 DEGs annotated in focal adhesion, 27 DEGs annotated in phagosome, 26 DEGs annotated in pathways in cancer, 25 DEGs annotated in ECM‐receptor interaction, 23 DEGs annotated in protein digestion and absorption, 20 DEGs annotated in oxidative phosphorylation, 17 DEGs annotated in lysosome, and 16 DEGs annotated in cell adhesion molecules.